Migration and Remittances in Moldova - Cuc, Milan (International Monetary Fund, 2006)
Labor migration and remittances, which have increasingly become a part of the global landscape, have profound economic and social consequences. Moldova, a small low-income country where an estimated one-third of the economically active population has been working abroad, is an interesting illustration of this trend. Drawing on household survey data, this Special Issues paper explains why Moldovan workers go abroad and how their remittances are used. With this background, it provides insights into policy challenges of coping with, and maximizing benefits from, international labor mobility and the large inflows of remittances.